DEVELOPMENT OF THE HERITAGE CENTER AS BANKRUPTCY CURATOR - Wijayanta, Tata; Adistia, Sheva Trisanda (Jurnal Pembaharuan Hukum, 2024)
This study aimed to find out and analyze the implications of the regulation of the Curator in Law No. 37 of 2004 on the Semarang Heritage Agency and the development of the Heritage Agency as bankruptcy curator. This study was empirical normative legal research that combined normative legal research and empirical legal research presented in a descriptive qualitative analysis. This research found that the change in Law No. 37 of 2004 was to add another curator besides the Heritage Agency. The results of the study and discussion show that the implication of setting the curator as the administrator and insolvency of bankruptcy assets is that the number of cases handled by the institution is divided into two, but in practice it is less than the curator and the developments that occur at the Property and Heritage Agency of Semarang in general are with the tasks of administering third party money and specifically the separation of duties on heritage and state curator (bankruptcy).